Hybrid Hydro-pyrometallurgical Process for Zn Recovery from Electric Arc Furnace Dust. Issue 1 (1st August 2022) - Bayoumi, R.A.; Abdelmonem, N. M.; Soliman, M. A.; Ismail, I.M.; Refaat, A. A.
Abstract: Electric arc furnace dust (EAFD) which is considered hazardous waste, contains significant amounts of Zinc (Zn), iron (Fe), and some dangerous elements. Zn exists in the dust as Zinc Oxide (ZnO) and Zinc Ferrite (ZnFe2 O3 ) which is difficult to be leached with traditional methods. The main objective of the suggested process is to recover Zn from EAFD by using a hybrid pyro/hydrometallurgical method. This method includes mixing cement dust and EAFD and heating the mixture in a pyrometallurgical treatment step to convert ZnFe2 O3 to ZnO. This step is followed by leaching the treated dust with sodium hydroxide (NaOH) solution using different Solid/Liquid (S/L) ratios through different time intervals in a hydrometallurgical treatment step. Finally, Zn-metal can be recovered from the leached solution in an electrochemical step (electro-winning). About 82 % of the Zn originally presented in the EAFD sample was successfully extracted by using a treatment mixture of 2:1 cement dust: EAFD at 1000 °C for 2 hrs., then leaching with 2M NaOH solution with an S/L ratio of 1/20 for 6 hrs. at a stirring rate of 250 rpm.